APLIKASI CERDAS ANDROID UNTUK PEMILIHAN MENU GIZI SEIMBANG PENCEGAH STUNTING DINI MENGGUNAKAN CERTAINTY FACTOR - Nurul Afni; Yola Permata Bunda (Smart Education, 2025)
Abstract: Stunting is a condition of growth failure in toddlers due to chronic malnutrition, especially during the First 1000 Days of Life (HPK). This issue is closely related to the nutritional intake of pregnant women, history of recurrent illnesses, and improper nutritional content in daily food menus. The Indonesian government's efforts to reduce stunting prevalence include nutritional interventions, counseling, and improved sanitation. However, limited access to balanced nutritional information remains a challenge for parents. This study aims to design an Android-based expert system using the Certainty Factor (CF) method to help parents detect early symptoms of stunting and select balanced nutritional menu for children. Data were obtained from nutritionists and health workers as the basis for recommendations. The calculation results using Certainty Factor method showed a stunting risk level of 0.773004 or 77.3%, indicating a high risk. The best recommended menu for this risk level is red rice, steamed fish, broccoli, oranges, and cheese with a certainty value of 0.34984. The developed expert system provides quick, accurate, and interactive recommendations, making it easier for parents to make decisions regarding their children's nutrition. In conclusion, the implementation of the Certainty Factor method in an Android application is effective as an educational medium and early detection tool for stunting, while also supporting sustainable stunting prevention efforts in society. Keyword: Stunting; Expert System; Certainty Factor; Nutrition; Android. Abstrak: Stunting merupakan kondisi gagal tumbuh pada balita akibat kekurangan gizi kronis, terutama pada 1.000 Hari Pertama Kehidupan (HPK). Masalah ini erat kaitannya dengan asupan gizi ibu hamil, riwayat penyakit berulang, dan gizi pada menu asupan makanan yang kurang tepat. Upaya pemerintah Indonesia dalam menurunkan prevalensi stunting dilakukan melalui intervensi gizi, penyuluhan, hingga perbaikan sanitasi. Namun, keterbatasan akses informasi gizi seimbang bagi orang tua masih menjadi kendala. Penelitian ini bertujuan merancang sistem pakar berbasis Android dengan metode Certainty Factor (CF) untuk membantu orang tua mendeteksi dini gejala stunting sekaligus memilih menu makanan bergizi seimbang bagi anak. Data diperoleh dari pakar gizi dan tenaga kesehatan sebagai dasar dalam penentuan rekomendasi. Hasil perhitungan menggunakan metode Certainty Factor untuk mengetahui Tingkat risiko gejala stunting yang dialami pengguna dan hasil akhir tingkat risikonya adalah 0,773004 atau 77,3 %, dengan status risiko tinggi, risiko ini menunjukkan menu terbaik yaitu nasi merah, ikan kukus, brokoli, jeruk, dan keju dengan nilai kepastian 0,34984. Sistem pakar yang dibangun mampu memberikan rekomendasi cepat, akurat, dan interaktif, serta memudahkan orang tua dalam pengambilan keputusan terkait gizi anak. Kesimpulannya, penerapan metode Certainty Factor dalam aplikasi Android efektif sebagai media edukasi dan deteksi dini stunting, sekaligus mendukung upaya pencegahan stunting secara berkelanjutan di masyarakat. Kata kunci: Stunting; Sistem Pakar; Faktor Kepastian; Gizi; Android.